Mermaid beach - Roberts, Sheila, 1951- (Roberts, Sheila, 1951- Moonlight Harbor series., 2023)
"Bonnie Brinks and her all-woman band, The Mermaids, are the pride of Moonlight Harbor. They're the house band at The Drunken Sailor, and that's just the right amount of fame for Bonnie. A lifetime ago, she went to Nashville to make it big, but she returned home with a broken heart and broken dreams. Now she's got a comfortable life and a brilliant daughter, Avril, who plays for The Mermaids alongside Bonnie and Bonnie's mother, Loretta. Avril has big dreams of her own. Her life in Moonlight Harbor is good--she loves singing and playing guitar with The Mermaids, and she has the sweetest, most loyal boyfriend a girl could ask for--but it all feels so ... small. She can't help wondering if there's something more out there for her. And she doesn't understand why her mom won't support her going to Nashville to find out. Meanwhile, Bonnie threw in the towel on her love life long ago, but Loretta sure hasn't. She's determined to be swept off her feet, and she wants the same for her daughter. When the hunky new owner of The Drunken Sailor turns the tables on the band and Avril announces she's leaving Moonlight Harbor, Bonnie's comfortable life seems to be drifting away. Will these three generations of Mermaids find their happy endings on the Washington coast? Or will the change in the winds leave them all shipwrecked?"--